Pengaruh Pengetahuan tentang Konsep Ekosistem dalam Pembelajaran Lingkungan Outdoor dan Indoor Terhadap Perilaku Berwawasan Lingkungan Siswa - Evita Anggereini; Made Putra Irawan (Universitas Jambi, 2016)
This research aim to find out the effect of knowledge of ecosystem concept in outdoor and indoor environmental learning to responsible environmental students behavior. The research was conducted in SMAN 5 Bekasi using experiment methods. This researh nvolving 70 students chosen by using cluster random sampling. The data analysis and interpretation indicated that: 1.Overall, there is not effect between of the ecosystem concept knowledge to responsible environmental students behavior. 2. Students with high knowledge about ecosystems concept who treated with outdoor environmental learning is higher than indoor in the responsible environmental behavior of students 3. Students with low knowledge about ecosystems concept who treated with outdoor environmental learning is lower than indoor in the responsible environmental behavior of students Therefore, indoor and outdoor environmental learning implemented in school must be attentionknowledge of ecosystem concept in order to effect to responsible environmental students behavior. Key words: outdoor and indoor environmental learning, knowledge of ecosystem concept, responsible environmental students behavior